Phase change materials in microactuators: Basics, applications and perspectives - Wilhelm, E.; Richter, C.; Rapp, B.E. (Sensors and actuators. A. Physical., 2018)
During the last decades micro electro mechanical systems (MEMS) have been subject to intensive research. In many cases active components, e.g., for regulating fluid flow or generating movement need to be included in the system design to ensure controlled operation. However, conventional actuators can seldom be used because their efficiency dec reases when their size is minimized. On the other hand miniaturization allows usage of a broad band of actuators that are inefficient in the macroscopic world. A significant amount of these actuators relies on phase change phenomena. The most intriguing fact about these transitions is their reversible nature which is associated to a pure physical transition. Facing an increasing amount of papers concerning phase change triggered micro actuation designers and operators of MEMS devices are often unable to decide which actuation principle is best-suited for their specific application. By summing up the content of more than 400 publications this review intends to provide designers as well as users of MEMS with the knowledge necessary for building efficient phase change driven actuators. For doing so the physical principles underlying each phase change phenomenon, which has been used for setting up MEMS, are introduced, followed by a thorough discussion of suitable materials that undergo the specific phase change. In order to enable the reader to choose the material best-suited for the target application the physical properties of more than 240 phase change materials, including some materials that have never been used in MEMS but are known from other research fields, e.g., energy storage, are listed within the review. With a focus on the physical working principle, the review highlights actuator concepts which have been used as printer heads, valves, pumps, grippers, actuators in drug delivery devices, devices for endoscopic surgery, aerospace engineering, and several other applications. The features of these actuators are compared in comprehensible tables in order to allow operators to quickly decide which actuator they could use for their specific application.